Real and permanent minimum wages - Michael R. Strain; Peter Brummund (American Enterprise Institute (AEI), 2016)
We study heterogeneity in minimum wage policy design and in the employment effects of minimum wage increases. Specifically, we study whether indexing minimum wages to inflation and differences in county-level wages and mobility rates lead to heterogenous employment effects following minimum wage increases. We find evidence that they do. To the best of our knowledge, this paper is the first to empirically study inflation indexing. Our preferred specifications imply that the disemployment effect of indexing minimum wages to inflation is over 2.5 times the magnitude of the disemployment effect associated with nominal minimum wage increases. We also find variance in the effect of minimum wage increases on employment across low- and high-wage counties – employment in low-wage counties is considerably more sensitive to minimum wage increases than employment in high-wage counties. And we provide preliminary evidence that less mobile counties have larger disemployment effects from minimum wage increases than higher mobility counties.
Keywords: A; 330; Minimum Wage